Long-life lithium-sulfur batteries with high areal capacity based on coaxial CNTs@TiN-TiO2 sponge - Hui Zhang (Nature Portfolio, 2021)
It is challenging to optimize catalytic heterostructures for lithium sulfur (Li-S) batteries. Here, authors prepare nanometer-scale TiN-TiO2 heterostructures via atomic layer deposition on carbon nanotube sponge to realize stable Li-S batteries with high areal capacity and improved rate capability.